2019
DOI: 10.3389/fimmu.2019.02903
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression Networks Identify DHX15 RNA Helicase as a B Cell Regulatory Factor

Abstract: Genome-wide co-expression analysis is often used for annotating novel gene functions from high-dimensional data. Here, we developed an R package with a Shiny visualization app that creates immuno-networks from RNAseq data using a combination of Weighted Gene Co-expression Network Analysis (WGCNA), xCell immune cell signatures, and Bayesian Network Learning. Using a large publicly available RNAseq dataset we generated a Gene Module-Immune Cell (GMIC) network that predicted causal relationships between DEAH-box … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…In recent years, RNA helicases have gained notoriety due to their role in cell maintenance, controlling many biological processes, including cell differentiation and apoptosis 9 . Also, several groups have linked the defects in helicase functioning with cancer, infectious diseases, immune response, and neurodegenerative disorders 2,10 . For instance, recent studies have shown that the deregulated expression of an increasing number of these enzymes usually appears in many types of tumors 11,12 , hence being related to carcinogenesis and cancer progression [13][14][15][16][17] .…”
mentioning
confidence: 99%
“…In recent years, RNA helicases have gained notoriety due to their role in cell maintenance, controlling many biological processes, including cell differentiation and apoptosis 9 . Also, several groups have linked the defects in helicase functioning with cancer, infectious diseases, immune response, and neurodegenerative disorders 2,10 . For instance, recent studies have shown that the deregulated expression of an increasing number of these enzymes usually appears in many types of tumors 11,12 , hence being related to carcinogenesis and cancer progression [13][14][15][16][17] .…”
mentioning
confidence: 99%
“…The fundamental idea behind this analysis was to shed some light into gene-gene interactions underpinning MS disease with regard to cause and effect ( 36 ). In this study, we reused GSE17048 experiment data which contained the profiled mRNA expression for all known genes in whole blood from 144 health individuals, 99 with MS (43 PPMS, 36 RRMS, and 20 SPMS).…”
Section: Resultsmentioning
confidence: 99%
“…The results were analyzed using the 2 − Ct method (35). In this study, beta-actin gene (as a reference gene) and S100A6, TUBA1C, and LASP1 genes [as target genes (TRG)] and CT data from real-time expression of TUBA1C, LASP1, and S100A6 were statistically analyzed (P < 0.05) by REST 2009 software.…”
Section: Quantitative Real Time Pcr Analysismentioning
confidence: 99%
“…The fundamental idea behind this analysis was to shed some light into gene-gene interactions underpinning MS disease with regard to cause and effect. The bnlearn package was used to nd the gene regulatory network behind this disease [22]. The results of comparison of the network structures determined from various algorithms, including Hill Climbing, Tabu Search, Max-Min Hill Climbing, and Restricted Maximize algorithms with different scoring functions, are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%